Kewenangan Badan Pengawas Pemilu Dalam Penanganan Tindak Pidana Pemilihan Umum Tahun 2024 (Studi pada Bawaslu Kota Palangka Raya) - Harvest Magabetua Sinaga; Heriamariaty; Fransisco; Kiki Kristanto; Rico Septian Noor; Syamhudian Noor (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2026)
The enforcement of criminal law in general elections is an important element in ensuring elections that are honest, fair, and have integrity. The Election Supervisory Body (Bawaslu) plays a strategic role in handling alleged election crimes through the Integrated Law Enforcement Center (Sentra Gakkumdu). However, in practice, the handling of election criminal offenses still faces various challenges that affect the effectiveness of law enforcement. This study aims to analyze the obstacles faced by the Election Supervisory Body of Palangka Raya City in handling election criminal offenses during the 2024 General Election. This research employs an empirical legal research method with a qualitative approach. Data were obtained through interviews with relevant parties and documentation studies of laws and regulations and official documents related to election crime cases. The results indicate that several obstacles were encountered, including limited human resources, coordination issues among institutions within Sentra Gakkumdu, differences in legal interpretation among law enforcement agencies, and budget limitations. These conditions indicate that the handling of election criminal offenses has not yet been implemented optimally.